Early Encounters: Understanding Early Onset Drug Misuse among Youth - Mutia Rahmah; Annisa Intan Sulistyani (Indonesian Journal of Global Health Research, 2026)
Adolescents experience a transition from childhood dependence to adult independence, which is often accompanied by a search for identity, exploration of the social environment, and increased curiosity about new things, including risky behavior, namely drug abuse. Based on data obtained at the preliminary study stage at the BNN Banjarbaru City, two junior high schools were found with the most significant number of students who had ever abused drugs. This study aims to determine the description of drug abuse and determine the relationship between respondent characteristics and drug abuse in adolescents. This study employed a quantitative descriptive approach using a cross-sectional design conducted at SMP “X” in Banjarbaru City.  Results: The Simple Random Sampling technique was used, and 70 students were obtained as respondents. The instruments used were demographic questionnaires and ASSIST Young 10-14 and ASSIST Young 15-17. Data analysis was carried out univariately and bivariately (chi-square). There was a significant relationship between age and tobacco (p-value = .036) and alcohol ((p-value = .040). There was no relationship between gender and tobacco (p-value = 0.153) and alcohol ((p-value = 0.363). Prevention and intervention programs should pay special attention to the dangers of tobacco/vaping and alcohol, target adolescents to reduce moderate and high risks, and prevent initiation of use in non-risk groups.